Heavy drinking habits are associated with worse in-hospital outcomes in patients with acute coronary syndrome. (25th November 2020) - Tersalvi, G; Biasco, L; Radovanovic, D; Rickli, H; Roffi, M; Eberli, F; Moccetti, M; Jeger, R; Moccetti, T; Erne, P; Pedrazzini, G.B
Abstract: Introduction: The association between alcohol consumption and the occurrence of coronary heart disease is well described in literature. Data regarding the impact of regular alcohol consumption on in-hospital outcomes in the setting of acute coronary syndrome (ACS) are lacking. Purpose: We aimed to evaluate the impact of self-reported alcohol consumption on in-hospital outcomes in patients with ACS. Methods: Data derived from patients enrolled between 2007 and 2019 in the Acute Myocardial Infarction in Switzerland (AMIS) Plus registry were retrospectively analyzed. The primary endpoint was all-cause in-hospital mortality, while secondary endpoints were set as incidence of major adverse cardiac and cerebrovascular events (MACCEs). Outcomes comparisons according to quantity of daily alcohol intake were also performed. Results: Records concerning alcohol consumption were available in 25707 patients; 5298 of them (21%) fulfilled the criteria of regular alcohol consumption. Daily alcohol intake was reported in 4059 (77%), of these patients (regular drinkers) with 2640 light drinkers (≤2 drinks/day) and 1419 heavy drinkers (>2 drinks/day). Regular drinkers were predominantly male, younger, smokers, more comorbid and with a worse clinical presentation as compared to abstainers/occasional drinkers. In-hospital mortality and MACCEs of heavy drinkers were significantly higher compared to light drinkers (5.4% vs. 3.3% and 7.0% vs. 4.4%, both p=0.001). When tested together with GRACE risk score parameters, heavy alcohol consumption was independently associated to in-hospital mortality (p=0.004). Conclusions: Heavy alcohol consumption is an additional independent predictor of in-hospital mortality in patients presenting with ACS. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): Swiss Heart Foundation